Neoadjuvant or adjuvant immunotherapy in bladder cancer: biological opportunity or clinical utility?. Issue 5 (October 2022) - Petrelli, Fausto; Perego, Gianluca; Vavassori, Ivano; Luciani, Andrea
In urothelial cancer of the bladder, the introduction of immunotherapy with immune checkpoint inhibitors represents progress in the management of the disease's early and advanced stages. In particular, recent studies have implemented these drugs in the neoadjuvant and adjuvant phases to treat muscle-invasive bladder cancer. In some studies, patients received neoadjuvant immune checkpoint inhibitors alone (PURE and ABACUS) to treat muscle invasive bladder cancer, whereas other studies provided this therapy to cisplatin-ineligible patients. Furthermore, a large Phase III study (CheckMate 247) compared placebo with adjuvant nivolumab therapy in patients with high-risk urothelial cancer after neoadjuvant chemotherapy and surgery or surgery alone. Despite some uncertain niches (nonbladder, PD-L1-negative tumors, and node-negative resected cancers), certain biological opportunities (exploring new targets, evaluating in vivo pathologic response, focusing on biomarkers for response) and clinical uses (avoiding chemotherapy at all or in frail patients, attaining similar pathologic complete response rates as in cisplatin-based chemotherapy) are valid reasons for incorporating these agents into the therapeutic armamentarium of medical uro-oncologists.